Endoscopic electrochemotherapy for esophageal cancer: a phase I clinical study - Egeland, Charlotte; Baeksgaard, Lene; Johannesen, Helle Hjorth; Löfgren, Johan; Plaschke, Christina Caroline; Svendsen, Lars Bo; Gehl, Julie; Achiam, Michael Patrick (Endoscopy International Open, 2018)
Background and study aims Esophageal cancer is on the rise in the western world and the disease has a poor 5-year survival prognosis below 20 %. Electrochemotherapy is a treatment where a chemotherapeutic drug is combined with locally applied electrical pulses, in order to increase the drug’s cytotoxicity in malignant cells. This study presents the first results with electrochemotherapy treatment in esophageal cancer. Patients and methods In this first-in-human trial, six patients with advanced esophageal cancer were treated with electrochemotherapy using intravenous bleomycin. All side effects and adverse events (AEs) were registered and the patients were later evaluated with gastroscopy and 18F-fluorodeoxyglucose positron emission tomography/magnetic resonance imaging (18F-FDG PET/MRI). Results Treatment were well tolerated, main AEs being nausea, vomiting, oral thrush, pneumonia, retrosternal pain, fever, and hoarseness. No serious complications were observed. Five patients had a visual tumor response confirmed by gastroscopy. In two cases, these findings were confirmed with 18F-FDG PET/MRI as it revealed a reduction of total tumor mass. Conclusion Electrochemotherapy in patients with advanced esophageal cancer was conducted without major safety concerns. This study paves the way for larger studies, which may further elucidate response rates for and side effects of this new treatment.